3D 인체 스캔 데이터를 이용한 11~15세 성장기 여성의 유방형태에 따른 유형 분류 - 한정정; Tingting Han; 송화경; Hwa Kyung Song; 이규선; Kyu Sun Lee (Fashion & textile research journal, 2017)
The purpose of this study is to analyze and classify breast shape of women aged 11~15 using 3D body scan data. In this study, 250 women’s body scans were selected from the 6th Size Korea dataset, and 30 items from each of the scan were measured using RapidForm XOR 3 program. The principal component analysis and cluster analysis were conducted using statistical program SPSS 17.0. The five principal components were identified; breast drooping and breast capacity, size from chest to under bust area, breast protrusion, breast height, and under breast angle & outer distance of breast. As the results of cluster analysis, woman's breast types were classified into four types. The breast type 1 was pro-trusion type (25.1%) which is considered as the breast maturity stage. The breast type 2 had the most drooped breast covering a large area (20.2%). The breast type 3 had the least prominent breast with a highest nipple point, which was considered as the early breast development stage (38.9%). The breast type 4 had the obesity of the chest and breast cir-cumferences with the slightly prominent and the least drooped breast (15.8%). This study can provide fundamental infor-mation to develop sizing system and brassiere pattern for junior girls.